Potensi Bangkitan Perjalanan Berbasis Guna Lahan Sekolah - Putra, Rahmad Syah; Putra, Sasana; Purba, Aleksander (Universitas Lampung, 2018)
AbstractCitizen growth will cause the increasing of amount trip due to fullfil the needs. School is a place that students go to, to get the education. Those activities can cause human movements and further can cause traffic jam if there are no proper configurations. The main aim of this study is to know the potential trip generation that caused by high schools in Bandar Lampung, to analize factor that affected by student movements and make the trip generation that caused by school’s function in Bandar Lampung. The main aim of this study is to know the potential trip generation that caused by high schools in Bandar Lampung, to analize factor that affected by student movements and make the trip generation that caused by school’s function in Bandar Lampung.The data were drawn from the responses of quesionaire that given to students of 4 high schools in bandar lampung and itsrelationship between transportation modes, vehicles ownership and pocket money. The data analysis is using category analysis and comparison descriptive. Trip generation from the category analysis counts from kepemilikan kendaraan, pemilihan moda dan besaran uang saku as one of factor that affected. The results of the category analysis obtained the total movement of students from the four schools that have been studied is 1259 movementsKeywords: high school students, trip generation, category analysis. AbstrakPertumbuhan penduduk akan mengakibatkan meningkatnya jumlah perjalanan guna memenuhi berbagai kebutuhan. Sekolah merupakan tempat tujuan aktivitas pelajar untuk memenuhi kebutuhan pendidikan. Aktivitas tersebut dapat menyebabkan perpindahan manusia dalam satu waktu dan kemudian hari dapat menimbulkan masalah seperti kemacetan apabila tidak dilakukan pengaturan. Tujuan penelitian ini adalah untuk mengetahui potensi bangkitan dan tarikan perjalanan yang ditimbulkan dari dan oleh sekolah menengah atas di Bandar Lampung, menganalisis faktor yang mempengaruhi pergerakan pelajar dan membuat model bangkitan yang diakibatkan fungsi sekolah di Bandar Lampung. Pengambilan data dilakuan dengan pembagian kuesioer kepada pelajar di empat sekolah yang telah ditentukan. Pertanyaan-pertanyaan yang diajukan mengenai asal tujuan perjalanan, moda transportasi, kepemilikan kendaraan serta uang saku. Kemudian dilakukan analisis data yaitu analisis kategori dan desktiptif komparatif Model bangkitan yang diperoleh dari hasil analisis kategori dihitung dengan kepemilikan kendaraan, pemilihan moda, dan besaran uang saku sebagai faktor yang mempengaruhinya. Hasil dari analisi kategori didapatkan pergerakan total pelajar dari keempat sekolah yang telah diteliti adalah sebesar 1259 pergerakan. Kata kunci : pelajar SMA, model bangkitan, analisa kategori.